The Indian Ocean in China’s Maritime Silk Road (MSR) Initiative: India’s Catch-22 Situation - Borah, Rupakjyoti (WILAYAH: The International Journal of East Asian Studies, 2016)
The Indian Ocean is hugely important for the health of India’s economy as the country is a net energy importer and since ancient days, Indian customs and influence have spread to nations far and wide through the maritime realm. However, of late, China has been trying to wade into what India has traditionally seen as its own backyard. China’s Maritime Silk Road (MSR) initiative, which seeks to increase Beijing’s influence in the Indian Ocean region, is a step in this direction. This article seeks to analyze how India should respond to the MSR. It will weigh the costs and benefits of New Delhi joining/staying out of the MSR and will lay down what should be India’s response.